Review: Animal‐assisted intervention for children with attention‐deficit/hyperactivity disorder – a systematic review and meta‐analysis. - Yu, Shuxin; Xue, Hui; Xie, Yuqing; Shao, Guanyue; Hao, Yihui; Fan, Lijun; Du, Wei (Child & Adolescent Mental Health, 2025)
Background: Animal‐assisted interventions (AAIs) have emerged as a promising nonpharmacological intervention option for children diagnosed with attention‐deficit/hyperactivity disorder (ADHD). However, recent systematic reviews have been primarily narrative. Additionally, the pooled effectiveness of AAIs was absent from these systematic reviews. Methods: We conducted a comprehensive systematic review and meta‐analysis, searching multiple databases, including Web of Science, MEDLINE, CINAHL, Scopus, PsycINFO, EMBASE and Cochrane, from inception of the databases to March 2024. We retrieved 17 randomised controlled trials or quasi‐experimental studies and used Review Manager 5.4.1 software to perform a meta‐analysis of the effects of AAIs in treating children with ADHD. We conducted a set of random‐effects meta‐analyses to estimate standardised mean differences (SMD) with 95% confidence intervals (CI) using subgroup data by different outcome domains extracted from eight randomised controlled trials, in relation to changes in behavioural, mental and physical functioning in a total of 307 children with ADHD before and after the intervention. Results: In comparison with non‐AAI groups, AAIs significantly improved attention problems in children with ADHD (SMD = −0.42, 95% CI = −0.71 to −0.13), self‐esteem (0.46, 0.14 to 0.78), learning and cognition problems (−0.69, −0.98 to −0.39) and motor proficiency (0.77, 0.11 to 1.42). The pooled effect of AAIs on the severity of ADHD symptoms in the experimental group was not significantly different from the effect of conventional treatments in the control group (0.10, −0.31 to 0.52). Similarly, AAIs had no significant positive effects on social interaction (−0.22, −0.51 to 0.06), social skills (−0.32, −0.87 to 0.24), problematic behaviours (−0.10, −0.54 to 0.35) or emotional problems, including depression and anxiety (−0.13, −0.51 to 0.24). Conclusions: As an ADHD management strategy complementary to gold‐standard approaches, such as medication or multimodal interventions, AAIs did not appear to be more effective in improving the majority of core ADHD outcomes in children. Future studies should incorporate rigorous study designs with large sample sizes and a standard protocol to achieve more valid and reliable conclusion.